Health misinformation of the grades five and six pupils - Rodriguez, Paz Pereyra
This study aimed to identify the health misinformation prevalent among the Grade V and VI pupils of Bato East and West districts in Catanduanes during SY 1976-1977. Related studies in the Philippines and abroad were reviewed. The normative survey method of research was utilized in this study. A true-or-false type of survey instrument was administered to 502 Grades V and VI pupils who were selected by stratified random sampling. The highest percentage of acceptance of the most prevalent health misinformation was found in the areas of prevention and control of diseases and safety and first aid followed in descending order by personal health, dental health, home, school and community health, and foods and nutrition.